TOP-QUARK SEARCH WITH THE D0 1992-1993 DATA SAMPLE - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Admas, M; Ahn, S; Aihara, H; Alitti, J; Alvarez, G; Alves, G; et al. (1995)
We present results on the search for the top quark in pp̄ collisions at s =1.8 TeV with an integrated luminosity of 13.5±1.6 pb-1. We have considered tt̄ production in the standard model using electron and muon dilepton decay channels (tt̄→eμ+jets, ee+jets, and μμ+jets) and single-lepton decay channels (tt̄→e+jets and μ+jets) with and without tagging of b quark jets. An analysis of these data optimized for top quark masses below 140 GeV/c2 gives a lower top quark mass limit of 128 GeV/c2. An analysis optimized for higher top quark masses yields 9 events with an expected background of 3.8±0.9. If we assume that the excess is due to tt̄ production, and assuming a top quark mass of 180 GeV/c2, we obtain a cross section of 8.2±5.1 pb. © 1995 The American Physical Society.